White beam X-ray Diffraction Topography (WBXDT) Studies of Bridgman Grown CdZnTe Crystals. Issue 1792 (22nd May 2015) - Babalola, Stephen; Uba, Samuel; Hossain, Anwar; Camarda, Giuseppe; James, Ralph; Montgomery, Trent
ABSTRACT: CZT is a semiconductor material that promises to be a good candidate for uncooled gamma radiation detectors. However, to date, we are yet to overcome the technological difficulties in production of large size, defect-free CZT crystals. The most common problem is accumulation of Tellurium precipitates as microscopic inclusions. These inclusions influence the charge collection through charge trapping and electric field distortion. We employed high energy transmission X-ray diffraction techniques to study the quality of the CdZnTe crystals grown by Bridgman Technique. Crystallinity and defects within two different growth set-ups, i.e. with and without choked seeding, were compared by imaging the crystal orientation topography with white beam X-ray diffraction topography (WBXDT). The X-ray diffraction topography results show high correlation with large-area infrared transmission images of the crystals. Grain boundaries that are highly decorated with Te inclusions are observed. Characteristic Te inclusion arrangements as a result of growth conditions are discussed. We also measured the electronic properties of the detectors fabricated from ingots grown using two Bridgman processes, and observed a reduction in electrical resistivity of choked-seeding-grown CdZnTe crystals. Our results show that although choked seeding technique holds a promise in the realization of high quality mono-crystalline CdZnTe, current growth parameters must be improved to obtain defect-free crystals. These results are helpful to attain optimal seeding process for Bridgman-growth of large single crystals of CdZnTe.